Kesiapan Akreditasi Dalam Perspektif Manajemen Pendidikan Islam Di MTs Assuruur - Rhani Fuji Lestari; Mulyawan Safwandy Nugraha (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This study is motivated by the growing urgency to improve the quality and accreditation of Islamic schools as key indicators of educational excellence in the modern era. The main objective of this research is to analyze the accreditation readiness of MTs Assuruur Pameungpeuk, Bandung Regency, based on the fundamental principles of Islamic Educational Management (MPI), which include four managerial functions: takhthith (planning), tanzhim (organizing), tanfidz (implementation), and taqwim (evaluation). Using a descriptive qualitative approach and a case study method through interviews, observations, and document analysis, the findings reveal that the integration of Islamic values within managerial functions significantly enhances accreditation readiness. These values foster a culture of quality, accountability, and professionalism grounded in spirituality (itqan and amanah). The study concludes that successful accreditation depends not only on administrative completeness but also on the internalization of MPI’s spiritual values in school management. The findings contribute to the theoretical development of Islamic educational quality management and offer practical insights for creating accreditation models rooted in Islamic. Keywords: Madrasah Accreditation, Islamic Educational Management, MPI, Educational Quality, Spiritual Values   AbstrakPenelitian ini dilatarbelakangi oleh pentingnya peningkatan mutu dan akreditasi madrasah sebagai tolok ukur kualitas pendidikan Islam di era modern. Tujuan utama penelitian ini adalah untuk menganalisis kesiapan akreditasi MTs Assuruur Pameungpeuk Kabupaten Bandung berdasarkan prinsip dasar Manajemen Pendidikan Islam (MPI) yang mencakup empat fungsi utama: takhthith (perencanaan), tanzhim (pengorganisasian), tanfidz (pelaksanaan), dan taqwim (evaluasi). Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode studi kasus melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan nilai-nilai Islam dalam fungsi manajerial madrasah berkontribusi signifikan terhadap peningkatan kesiapan akreditasi, terutama dalam membangun budaya mutu, tanggung jawab, dan profesionalisme berbasis spiritual (itqan dan amanah). Analisis juga mengungkap bahwa keberhasilan akreditasi tidak hanya ditentukan oleh kelengkapan dokumen administratif, tetapi juga oleh integrasi nilai-nilai spiritual MPI dalam setiap aspek manajemen madrasah. Temuan ini memperkaya kajian manajemen mutu pendidikan Islam serta memberikan dasar bagi pengembangan model akreditasi berbasis nilai Islami. Kata Kunci: Akreditasi Madrasah, Manajemen Pendidikan Islam, MPI, Mutu Pendidikan, Nilai Islami